Designing an ESP Syllabus for Housewives of Kosamba Town (Gujrat): A Pragmatic Approach - Ms. Arpitaben Keshavbhai Chauhan, Dr. Manoj Kumar, Dr. Priti Bala Sharma , Kaushal Kishore Sharma (South Eastern European Journal of Public Health, 2025)
This research paper explores the development of an English for Specific Purposes (ESP) syllabus tailored for housewives. The paper identifies the unique linguistic and pragmatic needs of housewives, focusing on their roles within domestic and social contexts, and proposes a syllabus that enhances their language skills for personal empowerment and societal engagement. The study adopts a needs-analysis approach, utilizing surveys and interviews to gather data, and discusses the theoretical and practical implications of designing a context-specific syllabus.